Molecular mechanisms of cholangiocarcinoma-cholangiocyte cell interactions in vitro - Owen, GJ (2023)
Cholangiocarcinoma is a highly aggressive cancer originating within the biliary tract. Whilst the role of the tumour microenvironment in CCA progression is well established, the function of surrounding cholangiocytes on CCA behaviour is often overlooked. Specifically, the effect of paracrine communication between cholangiocytes and cholangiocarcinoma cells has not been investigated previously. In this study, we provide evidence that cholangiocyte cells are a crucial paracrine modulator that influences the permissive or restrictive state to CCA progression.